FACE analysis as a fast and reliable methodology to monitor the sulfation and total amount of chondroitin sulfate in biological samples of clinical importance - Karousou, E.; Asimakopoulou, A.; Monti, L.; Zafeiropoulou, V.; Afratis, N.; Gartaganis, P.; Rossi, A.; Passi, A.; Karamanos, N. K. (MoleculesMolecules, 2014)
Glycosaminoglycans (GAGs) due to their hydrophilic character and high anionic charge densities play important roles in various (patho)physiological processes. The identification and quantification of GAGs in biological samples and tissues could be useful prognostic and diagnostic tools in pathological conditions. Despite the noteworthy progress in the development of sensitive and accurate methodologies for the determination of GAGs, there is a significant lack in methodologies regarding sample preparation and reliable fast analysis methods enabling the simultaneous analysis of several biological samples. In this report, developed protocols for the isolation of GAGs in biological samples were applied to analyze various sulfated chondroitin sulfate- and hyaluronan-derived disaccharides using fluorophore-assisted carbohydrate electrophoresis (FACE). Applications to biologic samples of clinical importance include blood serum, lens capsule tissue and urine. The sample preparation protocol followed by FACE analysis allows quantification with an optimal linearity over the concentration range 1.0-220.0 microg/mL, affording a limit of quantitation of 50 ng of disaccharides. Validation of FACE results was performed by capillary electrophoresis and high performance liquid chromatography techniques.
Karousou, EvgeniaAsimakopoulou, AthanasiaMonti, LucaZafeiropoulou, VassilikiAfratis, NikosGartaganis, PanagiotisRossi, AntonioPassi, AlbertoKaramanos, Nikos KengResearch Support, Non-U.S. Gov'tSwitzerland2014/06/14Molecules. 2014 Jun 12;19(6):7959-80. doi: 10.3390/molecules19067959.
Keywords: Chondroitin Sulfates/*analysis; Chromatography, High Pressure Liquid; Electrophoresis, Capillary/methods; Electrophoresis/*methods; Glycosaminoglycans/analysis